Improving Model-Driven Software Testing by using Formal Languages - Rosenfeld, Ilan (2019)
Model-Driven Testing or MDT is a new and promising approach for software testing automation that can significantly reduce the efforts in the testing cycle of a software development. It consists in a black box test that uses structural and behavioral models to automate the tests generation process. In this paper, we describe a tool that allows developers to translate a software model written in UML with OCL formal constraints to its corresponding Java code, automating the generation of strong test-cases codes and specifying them not only in Java language but also in two formal languages, which are OCL and Alloy. This tool provides more reliable support by amalgamating different techniques, which strengthens the testing process.